82.2k views
9 votes
Solve, using the correct order of
operations, when x = 7 and y = 3
(x – 3) + 2y

User Fargho
by
5.8k points

2 Answers

8 votes

Answer:


10

Explanation:

Sorry for messing it up last time. The format can be really weird

Step 1: Input x and y and solve


(x - 3) + 2y


(7 - 3) + 2 * 3


4 + 6


10

Answer:
10

User Mark Cramer
by
5.9k points
9 votes

Answer:

10

Explanation:

Since it given that:

x = 7 and y = 3

We can substitute x and y:

(7-3) + 2(3)

7 - 3 = 4

4 + 2(3)

2(3) = 6

4 + 6 =10

Thus the answer is 10.

[RevyBreeze]

User Mosh
by
6.1k points